2017
DOI: 10.14701/ahbps.2017.21.2.80
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted right hepatectomy via anterior approach for intrahepatic cholangiocarcinoma

Abstract: Major hepatic resection, especially right hepatectomy, has been successfully performed by specialized hepatobiliary centers using the robotic platform with low morbidity, conversion rates and outcomes comparable to laparoscopic and open surgery. The authors report a case of robotic-assisted right hepatectomy done for intrahepatic cholangiocarcinoma using anterior approach, after right portal vein embolisation for future liver remnant volume enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…All reviewers approved of the final set of included studies. In total, 11 studies reported data on 146 patients undergoing robotic surgery for cholangiocarcinoma (CC) [ 5 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], and 10 studies reported data on 113 patients undergoing robotic surgery for gallbladder cancer (GBC) [ 6 , 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…All reviewers approved of the final set of included studies. In total, 11 studies reported data on 146 patients undergoing robotic surgery for cholangiocarcinoma (CC) [ 5 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], and 10 studies reported data on 113 patients undergoing robotic surgery for gallbladder cancer (GBC) [ 6 , 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, few data are available on robotic liver resection for intra-hepatic cholangiocarcinoma, and no significant data on oncological outcomes are currently available (16,19,20).…”
Section: Primary Liver Tumorsmentioning
confidence: 99%